(untitled) (Eurasian Journal of Engineering and Technology, 2023)
The article is devoted to the maximum permissible indicators of physical chemical and dielectric properties of both newly filled and used transformer oil. Fresh oil poured into all types of oil-filled bushings, as well as operating oil for leaking bushings. Define the nominal voltage for the tap changer contactor